2004
DOI: 10.1590/s1519-566x2004000500004
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship, larval development and pupal weight of Anticarsia gemmatalis (Hübner) (Lepidoptera: Noctuidae) feeding on potential leguminous host plants

Abstract: PALAVRAS-CHAVE: Insecta, lagarta-da-soja, planta hospedeira, legume, soja, Glycine max ABSTRACT -In Brazil, the velvetbean caterpillar Anticarsia gemmatalis Hübner is multivoltine. Several overlapping generations occur with larvae feeding on alternate host plants in areas of warmer temperatures. In this study, the survivorship and development of A. gemmatalis larvae were evaluated on 17 species of cultivated and non-cultivated legumes in laboratory conditions. Larval survivorship on summer legumes varied from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
0
7
0
7
Order By: Relevance
“…Em laboratório, Sá et al (2009) não observaram diferenças significativas no perío-do larval de S. frugiperda alimentada com folhas de milho, sorgo, milheto, soja ou braquiária, confirmando os resultados aqui observados, exceto para soja e braquiária que foi significativamente maior do que nos demais. Panizzi et al (2004), avaliando em laboratório o desenvolvimento de lagartas de Anticarsia gemmatalis (Hübner), em 17 espécies vegetais, observaram que houve diferenças entre algumas leguminosas. Não houve diferença significativa no período de desenvolvimento larval de A. gemmatalis na soja, guandu, caupi e crotalária, mas foi maior nas larvas alimentadas em tremoço azul, ervilhaca e em ervilha.…”
Section: Período Larvalunclassified
“…Em laboratório, Sá et al (2009) não observaram diferenças significativas no perío-do larval de S. frugiperda alimentada com folhas de milho, sorgo, milheto, soja ou braquiária, confirmando os resultados aqui observados, exceto para soja e braquiária que foi significativamente maior do que nos demais. Panizzi et al (2004), avaliando em laboratório o desenvolvimento de lagartas de Anticarsia gemmatalis (Hübner), em 17 espécies vegetais, observaram que houve diferenças entre algumas leguminosas. Não houve diferença significativa no período de desenvolvimento larval de A. gemmatalis na soja, guandu, caupi e crotalária, mas foi maior nas larvas alimentadas em tremoço azul, ervilhaca e em ervilha.…”
Section: Período Larvalunclassified
“…Resultados experimentais sugerem que o desenvolvimento da LCM nas gramíneas Panicum maximum e Cynodon dactylon pode ter papel importante na dinâmica populacional de S. frugiperda no Norte da Argentina (Murúa & Virla 2004). Com base no desenvolvimento e na sobrevivência de lagartas de Anticarsia gemmatalis Hübner, Panizzi et al (2004) observaram diferenças signifi cativas entre 17 leguminosas cultivadas e não-cultivadas, sendo que as mais adequadas foram a soja, o guandu e o tremoço branco.…”
unclassified
“…A. gemmatalis was one of the dominant species in both sites. This Lepidopteran is the main defoliation pest of soybean crops in Brazil (Hoffmann-Campo et al 2000, Panizzi et al 2004, and hairy fleabane showed to be an important secondary host for this caterpillar, as well as to S. frugiperda. Although the latter species is the predominant pest in corn crops, in recent growing seasons, it has been observed damaging soybean leaves and pods (Barros et al 2010).…”
Section: Resultsmentioning
confidence: 99%